REVITALISASI MANAJEMEN KOPERASI UNTUK MEWUJUDKAN KESEJAHTERAAN ANGGOTA KOPERASI (Studi Pada Dinas Koperasi dan UKM Kabupaten Muna) - Sufiana Sufiana; Syamsul Alam; Jopang Jopang (Universitas Halu Oleo, 2019)
The purpose of this study was to determine the Implementation of Cooperative Revitalization in the Cooperative and SME Office of Muna Regency. The purpose of this study is to provide an overview of the implementation of the revitalization of cooperatives in the Muna Regency Cooperative and the UKM Office. This research was conducted at the Muna District Cooperative and the SME Institute. Data collection techniques used in this study are using primary data and secondary data. The data collected will be analyzed qualitatively.The results of the research are based on the indicators of the Members' Meeting, the Audit Board, Managers, People, Interests, Rules and Structures, showing that the Revitalization of Cooperative Management to Achieve the Welfare of Cooperative Members in the Cooperative Office of Muna Regency has an important role for the survival of members and communities. While in the management of cooperatives to realize the welfare of cooperative members in the Muna Regency Cooperative Office, it runs in accordance with applicable standards.